Blood on a Mosque: Religion, the Sacred, and the Finnish Criminal Court Process. - Äystö, Tuomas (Journal of Religion in Europe, 2017)
This article analyzes a Finnish criminal court process concerning a spattering of blood on a mosque. Initially ruled as a religious insult, the charge was eventually dropped on the grounds that the Islamic community in question did not have the proper legal personality. The article utilizes a non-normative discursive perspective to analyze the construction of 'sacredness' and the category of 'religion' in the legal process. First, it is argued that several officials were influenced by the prevailing discourses on religion and blood, as well as the meaning of 'sacred,' to the point where they contradicted the prevalent legalistic discourse. Second, the legalistic discourse observed in the final ruling demonstrates how the prohibition of religious insult is part of the Finnish association-oriented model for managing a society perceived as religiously diverse.